Compound-specific D/H ratios of lipid biomarkers from sediments as a proxy for environmental and climatic conditions - Sauer, P. E.; Eglinton, T. I.; Hayes, J. M.; Schimmelmann, A.; Sessions, A. L. (Geochimica Et Cosmochimica Acta, 2001)
Hydrogen isotope ratios (D/H) of lipid biomarkers extracted from aquatic sediments were measured to determine whether they can be used as a proxy for D/H of environmental water. Values of deltaD were determined by using a recently developed isotope-ratio-monitoring gas chromatograph-mass spectrometer system (irmGCMS) and were confirmed by conventional hydrogen isotopic measurements (i.e., combustion followed by reduction) on individual compounds isolated by preparative capillary gas chromatography. Diverse lipids (alkanes, n-alkanols, sterols, and pentacyclic triterpenols) were analyzed to examine hydrogen-isotopic controls on lipids of varying origin and biosynthetic pathway. For algal sterols (24-methylcholest-3 beta -ol, 24-ethylcholest-5,22-dien-3 beta -ol, and 4,23,24-trimethylcholesterol, or dinosterol), the fractionation between sedimentary lipids and environmental water was -201 +/- 10 parts per thousand and was similar in both marine and freshwater sites. In a sediment from a small lake in a forested catchment, triterpenols from terrestrial sources were enriched in D by 30 parts per thousand relative to algal sterols. Apparent fractionation factors for n-alkyl lipids were smaller than those of triterpenols and were more variable, probably reflecting multiple sources for these compounds. We conclude that hydrogen-isotopic analyses of algal sterols provide a viable means of reconstructing D/H of environmental waters. Results are less ambiguous than reconstructions based on analyses of kerogen or other operationally defined organic matter fractions. Copyright (C) 2001 Elsevier Science Ltd.
395npTimes Cited:209Cited References Count:64